PENGARUH ARANG AKTIF, BENZILADENIN, DAN KINETIN TERHADAP PERTUMBUHAN TUNAS JATI SOLOMON (Tectona grandis Linn. f) IN VITRO - Husen Hariadi; Yusnita Yusnita; Melya Riniarti; Dwi Hapsoro (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Tissue culture techniques can be used for propagation of uniformaly large teak solomon seeds.The purpose of this research was knowing the effect of activated charcoal, the addition of benzyladenine (BA) and combination of BA with 6-furfurylaminopurine (kinetin) to the growth of shoots of solomon teak in vitro. The solomon teak explants used were singlestem cuttings from aseptic shoots obtained from in vitro cultures. This research was conducted in laboratory with complete randomized design with 3 replications. The experimental treatment was a single factor consisting of basic MS medium (Murashige and Skoog, 1962), with 6 treatments: MS without growth regulator (control), MS without growth regulator + 2 g/l activated charcoal, MS + 0,1 m/l BA , MS + 0,2 m/l BA, MS + 0,1 m/l BA + 0,1 m/l kinetin and MS + 0,2 m/l BA + 0,1 m/l kinetin. Observation on the number of books/ shoots, number of leaves/ shoots, shoot/ bud height and visual apperance of culture was taken at 8 weeks after planting. The data were analyzed for variety and continue the separation of the LSD at 5% level. The results showed that in general, all six treatments could be used for propagation of in vitro teak solomon (Tectona grandis Linn. f) and produced at least 6,22 books/ shoots every 8 weeks. The best media were MS medium + 0,1 m/l BA and MS + 0,1 m/1 BA + 0,1 m/l kinetin, because it able to produce 7,78 books/ shoots. The highest number of leaves was obtained at the treatment of MS + 0,1 m/l BA, while the average shoots/ shoots produced were not different for all.